Juridical Dilemma of the Principle of Notary Prudence in the Verification of Foreign Documents After the Ratification of the Apostille Convention - Priyono, Vinza Rizqie Putra (Jurnal Indonesia Sosial Sains, 2026)
The ratification of the Convention Abolishing the Requirement of Legalisation for Foreign Public Documents (Apostille Convention) through Presidential Regulation Number 2 of 2021 has simplified the legalization of foreign public documents in Indonesia. However, the apostille system creates a juridical dilemma for notaries because it only certifies the formal authenticity of documents (signature, official capacity, seal) without guaranteeing the material truth of their contents. This study aims to analyze the juridical dilemma faced by notaries in verifying foreign documents, as well as their legal responsibilities and protections. This research employs a normative legal method using statutory (statute approach) and conceptual (conceptual approach) approaches, analyzing primary legal materials (UUJN, Perpres No. 2/2021, Permenkumham No. 6/2022, Apostille Convention 1961) and secondary legal materials (journals, books, legal commentaries). The findings show that notaries remain obligated to apply the principle of prudence when examining foreign documents, despite the presence of an apostille certificate. The apostille does not eliminate the notary's duty under Article 16 paragraph (1) letter a of UUJN to act thoroughly (cermat) and protect the interests of the parties. The research identifies three specific dilemmas: (1) conflicting verification standards between the apostille system and notary prudence; (2) absence of regulations governing verification limits for foreign documents; and (3) increased legal risk due to digitization and e-apostille implementation. The study concludes that legal protection for notaries remains repressive (post-dispute) rather than preventive, and harmonization of regulations is urgently needed to establish clear verification standards and limits of notary responsibility.